PENGOBATAN TRADISIONAL AKUPRESUR DI ERA MODERN PADA MASYARAKAT ABEPURA KOTA JAYAPURA PAPUA - Tamalonggehe, Yuliet M.; Deeng, Djefry; Mamosey, Welly E. (Universitas Sam Ratulangi, 2021)
Traditional medicine is one of the treatments that has been passed down from generation to generation as a cultural heritage in the health sector to overcome various diseases. Traditional medicine utilizes existing local wisdom so that it is believed to have no side effects from the ingredients given, quite easy to find, easy to make ingredients and fairly cheap. Acupressure which is used to stimulate the nerves in the affected organ is very influential in the treatment process so that with traditional acupressure treatment the disease is handled from the outside and also inside so that the impact is felt better. The results showed that traditional acupressure treatment in Abepura not only uses traditional medicine (herb) but sometimes uses medical medicine because traditional acupressure treatment in Abepura adapts to the modern era where there is also a sense of security and trust in the community because of the perceived impact on traditional acupressure treatment and also the good behavior of the healer.Keyword : Traditional medicine, Acupressure, and Modern era